Planning for Recreational Activities in Calabar City Centre - Ukene, Daniel (Obafemi Awolowo University, 2014)
Planning for recreational activities does not seem to be receiving serious attention from Policy makers in Nigeria. Although the Nigerian economy is currently undergoing serious crises, this should not affect planning for recreational activities. Intact, it has been observed that recreation has always constituted an important part of people's lives: in history no matter their level of poverty.